In Defense of a Social Value Requirement for Clinical Research. (February 2017) - Wendler, David; Rid, Annette
Abstract: Many guidelines and commentators endorse the view that clinical research is ethically acceptable only when it has social value, in the sense of collecting data which might be used to improve health. A version of this social value requirement is included in the Declaration of Helsinki and the Nuremberg Code, and is codified in many national research regulations. At the same time, there have been no systematic analyses of why social value is an ethical requirement for clinical research. Recognizing this gap in the literature, recent articles by Alan Wertheimer and David Resnik argue that the extant justifications for the social value requirement are unpersuasive. Both authors conclude, contrary to almost all current guidelines and regulations, that it can be acceptable across a broad range of cases to conduct clinical research which is known prospectively to have no social value. The present article assesses this conclusion by critically evaluating the ethical and policy considerations relevant to the claim that clinical research must have social value. This analysis supports the standard view that social value is an ethical requirement for the vast majority of clinical research studies and should be mandated by applicable guidelines and policies.